The Legal Status of Nikah Siri in the Indonesian Legal System: A Normative Examination of Islamic Law and the Marriage Law - Tiara Alpiani; Dadang Jaya (Institut KH Ahmad Sanusi (INKHAS) Sukabumi, 2026)
As Indonesian citizens, the implementation of marriage has been regulated in Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law. Legally, a marriage is declared valid if it is carried out according to religious provisions and is officially registered at the Office of Religious Affairs. However, in practice in society, there are still marriages only carried out based on religious provisions without being officially registered with government institutions, known as “nikah siri”. The research aims to determine the legal certainty of nikah siri. This research uses a normative approach through literature study to examine the position of nikah siri from the perspective of Islamic law and national law. The results show that nikah siri is a valid marriage practice from a religious perspective because it meets the requirements and pillars of Islamic law. However, in the context of positive Indonesian law, this marriage type is not legally recognized because it is not officially registered by the state. This lack of registration gives rise to various legal issues, particularly in terms of protecting the rights of women and children born from these marriages. They are at risk of not receiving legal rights such as birth certificates, inheritance rights, rights to support, and other protections. Although Islamic law does not require registration as part of the validity of a marriage, social and legal developments in Indonesia demand valid administrative evidence as a basis for legal protection. Therefore, marriage registration is not merely a formality, but a crucial step in realizing justice, legal certainty, and the common good in household and community life.